Pengembangan Media Mathchance untuk Pembelajaran Peluang di Sekolah Dasar - Mulyasaroh, Mulyasaroh; Ardita, Fahra Putri; Nulhakim, Lukman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop an interactive learning media called MathChance to improve elementary school students’ understanding of probability concepts. The method used in this study was Research and Development (R&D) with development stages including information gathering, planning, initial product development, limited and wider trials, product revision, and implementation. The research subjects were 31 fifth-grade elementary school students. Data collection techniques included observation, interviews, tests, and questionnaires. The results showed that the MathChance media effectively improved students’ learning outcomes, as indicated by the increase in the average score from 66.45 in the pretest to 86.45 in the posttest. The paired sample t-test results showed a significant difference between the pretest and posttest scores (p < 0.05). In addition, students’ responses to the use of the learning media were categorized as very good, with an average score of 4.63. In conclusion, the MathChance interactive learning media is feasible to be used as an alternative learning medium to improve students’ motivation and learning outcomes in probability learning at the elementary school level. Keywords: Borg & Gall, Learning Outcomes, MathChance, Interactive Learning Media, Probability.